Religious Traditions in Kuang Dalam: Uncovering Spiritual Meanings and Values - Aravik, Havis; Achmad Irwan Hamzani; Nur Khasanah (Publication and Inovasi Research, 2024)
Religious traditions are closely related to religious teachings and are an integral element of community life, particularly in Kuang Dalam. These traditions not only reflect spiritual expression but also play an important role in strengthening social solidarity and preserving cultural identity. This research uses a descriptive qualitative approach with ethnographic methods to understand the religious traditions of the Kuang Dalam community in depth, including birth, marriage and death traditions. Data were obtained through participatory observation, in-depth interviews and documentation, and analysed interpretively to explore the values, symbols and meanings of these traditions. The results show that religious traditions such as nujuh bulan, nunde keluagh, and marhabah in the birth cycle symbolise gratitude and prayers for the safety of mothers and children. Marriage traditions, including bepandas and cake auctions, emphasise the sacredness of marriage and community solidarity. Death traditions, such as ngurus mayit, reflect respect for the dead and social support for bereaved families. These traditions enrich spiritual life, strengthen social harmony and preserve local identity amidst modernisation